Volatile Essential Oils from Different Tree Species Influence Scent Impression and Physiological Response - Eri Matsubara; Naoyuki Matsui (Molecules)
The large number of underutilized tree residues in Japan is a matter of concern, and their appropriate application needs to be promoted. Trees are very diverse, and there are differences in the volatile essential oil compounds and biological activities among different tree species. However, the effects of these tree species’ characteristics on human sensitivity and mental and physical functionality remain underexplored. This study investigated the effects of essential oils from multiple tree species on subjective and physiological responses. The essential oils from nine tree species were tested, subjective scent assessments were conducted, and their effect on autonomic nervous activity was measured. The volatile profiles of the oils were analyzed using gas chromatography–mass spectrometry. Our findings revealed clear differences in the composition of volatile essential oils among species, which influenced the scent evaluation and individual preferences. We suggest that scent preferences have the potential to influence physiological responses. The findings indicate that volatile essential oils could play a potential role in making use of tree resources effectively, and they may also be beneficial for maintaining human health.